HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT DEPRESI PADA LANSIA DI PSLU BONDOWOSO - Tri Farisa Bheli Putra Ahmadiyanto; Lulut Sasmito; Khofi Hadidi (Jurnal Kesehatan dr. Soebandi, 2016)
Depression is sadness and worry in a long time accompanied by feelings of worthlessness. The cause of depression is the lack of positive reinforcement, especially in the elderly who lack support from his family often associated with depression syndrome. This study was to determine the relationship of family support with the level of depression in the elderly at UPT PSLU Bondowoso. This type of correlational research with obsevasional design. The research sample of 46 elderly using simple random sampling technique with age maching: 1) 60-64; 2) 65-69; 3) 70-74; 4) 75-79; 5) 80-84; 6) 85-89, with inclusion criteria willing to be respondents and can be measured family support and the level of depression. Analysis using Spearman-rank corellation with significance level α <0.05. The results of research on elderly family support at UPT PSLU Bondowoso in the May-June 2014 period showed that most of the family support was good (10.9%) and moderate family support (80.5%), and family support was less (8.7%) . Most of the minor depressions were (54.3%), and a small portion were not depressed (8.7%) and moderate depression (37.0%) and there were no major depressions. The Spearman-rank correlation test results showed a significant relationship between family support and the level of depression in the elderly in Bondowoso PSLU, with a value of 0,000 (p <0.05). Suggestions for families should provide full support to the elderly in the family in order to provide scope for socializing